Proximal Tibia Osteoarticular Allografts in Tumor Limb Salvage Surgery - Muscolo, D. Luis (Springer-Verlag, 2009)
BACKGROUND: Resection of large tumors of the proximal tibia may be reconstructed with endoprostheses or allografts with fixation. Endoprosthetic replacement is associated with high failure rates and complications. Proximal tibia osteoarticular allografts after tumor resection allows restoration of bone stock and reconstruction of the extensor mechanism, but the long-term failure rates and complications are not known. QUESTIONS/PURPOSES: We therefore determined (1) the middle- and long-term survival of proximal tibia osteoarticular allografts, (2) their complications, and (3) functional (Musculoskeletal Tumor Society score) and radiographic (International Society of Limb Salvage) outcomes in patients treated with this reconstruction. PATIENTS AND METHODS: We retrospectively reviewed 52 patients (58 reconstructions including six repeat reconstructions) who underwent osteoarticular proximal tibia allograft reconstructions after resection of a bone tumor. The minimum followup of the 46 surviving patients was 72 months (mean, 123 months; range, 10–250 months). Survival of the allograft was estimated using the Kaplan-Meier method. We documented outcomes using the Musculoskeletal Tumor Society functional scoring system and the International Society of Limb Salvage radiographic scoring system. RESULTS: Six patients died from tumor-related causes without allograft failure before the 5-year radiographic followup. At last followup, 32 of the 52 remaining allografts were still in place; 20 failed owing to infections, local recurrences, or fractures. Overall allograft survival was 65% at 5 and 10 years, with an average Musculoskeletal Tumor Society functional score of 26 points and an average radiographic result of 87%. CONCLUSIONS: Based on these data we believe proximal tibia osteoarticular allograft is a valuable reconstructive procedure for large defects after resection of bone tumors. LEVEL OF EVIDENCE: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.